2011
DOI: 10.1128/mcb.05020-11
|View full text |Cite
|
Sign up to set email alerts
|

1,25-Dihydroxyvitamin D3Ameliorates Th17 Autoimmunity via Transcriptional Modulation of Interleukin-17A

Abstract: A new class of inflammatory CD4؉ T cells that produce interleukin-17 (IL-17) (termed Th17) has been identified, which plays a critical role in numerous inflammatory conditions and autoimmune diseases. Interleukin-17A (IL-17A)-producing T cells are a subset of CD4 ϩ T cell lineage, termed Th17, distinct from Th1, Th2, and T regulatory (T reg ) subsets (52). IL-17 is involved in the pathogenesis of autoimmune inflammation and has been implicated in numerous autoimmune diseases, including systemic lupus erythemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
305
5
9

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 433 publications
(334 citation statements)
references
References 80 publications
15
305
5
9
Order By: Relevance
“…Those studies found very low Vdr gene expression in CD4 + Foxp3 + Treg cells, suggesting these cells may be relatively unresponsive to 1,25-(OH) 2 D 3 . In contrast, one report found that administering 1,25-(OH) 2 D 3 increased the percentage of CD4 + Foxp3 + Treg cells in the spleen and the CNS (56). This report included flow cytometric data from one animal, and did not tabulate and compare the variance in the results from all animals.…”
Section: Discussionmentioning
confidence: 99%
“…Those studies found very low Vdr gene expression in CD4 + Foxp3 + Treg cells, suggesting these cells may be relatively unresponsive to 1,25-(OH) 2 D 3 . In contrast, one report found that administering 1,25-(OH) 2 D 3 increased the percentage of CD4 + Foxp3 + Treg cells in the spleen and the CNS (56). This report included flow cytometric data from one animal, and did not tabulate and compare the variance in the results from all animals.…”
Section: Discussionmentioning
confidence: 99%
“…(1,25(OH)2D3) exerts immunomodulatory effects on T cells from patients with SR asthma patients, enhancing the impaired steroid-induced IL-10 response in these individuals (31), while others have highlighted the capacity of this molecule to inhibit Th17 responses (32)(33)(34)(35).…”
Section: Introductionmentioning
confidence: 99%
“…Because significant signal was not observed outside the dLNs and sites of immunization, the decline in signal after day 10 can be best explained by cell loss during the contraction phase of the immune response rather than the redistribution of 2D2-Luc cells to other tissues such as the CNS. The signal intensity approached the preimmunization levels by the time the vehicle-treated animals developed clinically apparent disease (day 14), suggesting that the endogenous Luc-negative MOG-reactive T H cells were the cells causing the disease. Importantly, no difference in the signal intensity and distribution was observed between the vehicle-and 1,25(OH) 2 D 3 -treated animals, indicating that 1,25(OH) 2 D 3 does not affect expansion of MOG-specific T H cells or their migration to the site of immunization.…”
Section: Ultiple Sclerosis (Ms) Is An Immune-mediated Demyelinatingmentioning
confidence: 98%
“…Moreover, 1,25(OH) 2 (13,14). No significant difference in the proportion of the CD25 + Foxp3 + Tregs was detected between the treatment groups at either EAE day 15 or 36 ( Fig.…”
Section: Ultiple Sclerosis (Ms) Is An Immune-mediated Demyelinatingmentioning
confidence: 99%